Improving the Link of the Gas and Smoke Protection Service on the Basis of Compressed Air Breathing Apparatus for Firefighters - Sh. E, Kurbanbaev; I. I., Mukhamedov (European Journal of Life Safety and Stability (2660-9630), 2022)
The study analyzes the search and rescue operations carried out by a link of the gas and smoke protection service of the Ministry of Emergencies. The relationship between the time of work and the flow rate of air in the cylinders of breathing apparatus with compressed air has been substantiated